1993
DOI: 10.1017/s0950268800057083
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of monoclonal antibodies against a type SAT 2 foot-and-mouth disease virus

Abstract: SummaryThis paper is the first to describe characterization of monoclonal antibodies (MAbs) against a South African Territories 2 (SAT 2) foot-and-mouth disease virus (isolate Rho 1/48). Twelve MAbs which neutralized homologous virus were characterized in indirect and sandwich ELISA using purified Rho 1/48 virus particles, subunits, trypsin-treated, and chemically denatured virus. All the Mabs inhibited haemagglutination by parental virus. Binding of the MAbs to 73 SAT 2 field isolates was measured in a sandwi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 19 publications
(17 reference statements)
0
46
0
Order By: Relevance
“…This epitope was highly conserved, Figure 1 The MAb RHO 7, 11, 27, 28, 37 and ZIM 108 formed another group. Crowther and colleagues [2] showed that MAb RHO 7, 27, 28 and 37 react with the same conformational epitope and it is likely that ZIM 108, a neutralizing MAb, also reacts at this site; this was strongly indicated in the MAb escape mutant study where ZIM 108 did not bind to escape mutants produced by MAb Rho 1/48, 7, 11, 27, 28 or 37, but bound to all other mutants. Fifty-three (85%) of the viruses in the study bound MAb from this group.…”
Section: Analysis Of Virusesmentioning
confidence: 98%
See 4 more Smart Citations
“…This epitope was highly conserved, Figure 1 The MAb RHO 7, 11, 27, 28, 37 and ZIM 108 formed another group. Crowther and colleagues [2] showed that MAb RHO 7, 27, 28 and 37 react with the same conformational epitope and it is likely that ZIM 108, a neutralizing MAb, also reacts at this site; this was strongly indicated in the MAb escape mutant study where ZIM 108 did not bind to escape mutants produced by MAb Rho 1/48, 7, 11, 27, 28 or 37, but bound to all other mutants. Fifty-three (85%) of the viruses in the study bound MAb from this group.…”
Section: Analysis Of Virusesmentioning
confidence: 98%
“…The binding of the South African MAb with selected RHO 1/48 MAb escape mutants, produced as described elsewhere [2], was also measured using the sandwich ELISA.…”
Section: Characterization Of Mabmentioning
confidence: 99%
See 3 more Smart Citations